‘FITNA’ IN EVERYDAY LIFE: Phenomena of the Digital Behavior of Indonesian Muslim Society on Dajjal Hadith - Putra, D.I Ansusa (ULUL ALBAB Jurnal Studi Islam, 2020)
Dajjal appearance discussion in the last decade has been the trending among Muslim. There are massive search for religious doctrines text on Dajjal in digital media. This is oriented towards certain views about the world, social and cultural conditions, political project, political subjectivity, attitudes, and practice or competence. The behavior affects social-political life through the contextualization of hadith about Dajjal. This study aims to obtain a complete picture of digital media behavior in understanding religious doctrines related to Fitna of Dajjal among Muslims. This article combines Muslim theory of Cosmopolitanism Khairuddin Aljunied and living hadith approach, supported by data from google trend search throughout 2019. The results showed that there were four digital behaviors of Indonesian Muslim related to Dajjal hadith, first, searching instantaneously; second, reviewing from internet; third, joining the contextualisation discussion; and fourth, liking the personalization and illustration. The most frequently sought topic is about the prayer to be protected from Fitna of Dajjal. In addition, the study also tried to prove that this digital behavior is formed massively because of supply and demand pattern. It means that there are groups producing Dajjal hadith in public sphere regularly since they are supported by the many interests of consumers.